Evaluasi dan Rekomendasi Perbaikan Usability pada System Autoworksys pada PT. Prima Berkat Gemilang dengan menggunakan Metode Heuristic Evaluation dan System Usability Scale (SUS) - Aditya Reza Firdaus; Niken Hendrakusma Wardani; Lutfi Fanani (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Autoworkys is a web-based back-office system developed by PT. Prima Berkat Gemilang to serve automotive companies the requirements in performing their operational activities. Autoworkys system has been used in various automotive companies that are spread throughout Indonesia, including Dipo Angkasa Motor, Eurokars Indonesia PT, Indonesian Jeep Station, etc. Based on the observations there are problems, that are the sparepart input form can not do a search for the description but the keyword id, so the user must input the keyword id as many as 10 digits and when creating a new user there is no command to input a password, the two problems are not in accordance with the principle of heuristic evaluation, namely help and documentation and recognition rather than recall. Given the large number of customers and the problems that the autoworkys system has, it is necessary to evaluate the system's usability. The methods used to evaluate the system's usability are Nielsen heuristic which involves IT experts and John Broke System Usability Scale (SUS) which involves user perceptions. The result of heuristic evaluation showed 53 problems with the most problems found on the H7 (Flexibility and efficiency of use) and the System Usability Scale showed a value of 67,25 which means â€œOKâ€ for the adjective ratings and â€œDâ€ for the grade scale. The autoworksys design improvement is done based on the guidelines and expert insight. The result showed a decrement from 53 problems to 1 problem and the System Usability Scale result showed an increment from 67,25 to 86,25 which means â€œEXCELLENTâ€ for the adjective ratings and â€œBâ€ for the grade scale.